Efficacy and Safety of a Fixed Combination of Cinnarizine 20 mg and Dimenhydrinate 40 mg vs Betahistine Dihydrochloride 16 mg in Patients with Peripheral Vestibular Vertigo: A Prospective, Multinational, Multicenter, Double-Blind, Randomized, Non-inferiority Clinical Trial - Scholtz, Arne W; Hahn, Ales; Stefflova, Bohdana; Medzhidieva, Daniela; Ryazantsev, Sergey V; Paschinin, Alexander; Kunelskaya, Natalia; Schumacher, Kai; Weisshaar, Gerhard (Clinical drug investigation, 2019)
BACKGROUND AND OBJECTIVE: Vertigo derived from peripheral vestibular disorders is quite frequently encountered in daily clinical practice and can be a severely disabling symptom associated with substantial impairment of health-related quality of life for the affected patients. Betahistine, a structural analogue of histamine and presumably the most widely prescribed anti-vertigo drug worldwide, has previously been shown to be an effective and safe treatment for these patients. The objective of the present study was to evaluate whether the fixed combination of cinnarizine and dimenhydrinate (Arlevert®) is non-inferior and thus a potentially useful alternative to betahistine dihydrochloride in the treatment of patients suffering from peripheral vestibular vertigo. METHODS: In this prospective, multicenter, double-blind, randomized, non-inferiority clinical trial, outpatients from 8 ENT clinics in Austria, Bulgaria, the Czech Republic and Russia were randomly assigned to receive three times daily one tablet of either the fixed combination cinnarizine 20 mg/dimenhydrinate 40 mg or betahistine dihydrochloride 16 mg for 4 weeks. Primary endpoint was the reduction of the mean vertigo score (MVS), a validated 12-item composite score defined as the mean of 6 vertigo symptoms (dystasia and walking unsteadiness, staggering, rotary sensation, tendency to fall, lift sensation, blackout) and 6 trigger factors for vertigo (change of position, bowing, getting up, driving by car/train, head movements, eye movement), after 4 weeks of therapy, as judged by the patient on a 5-point visual analogue scale (VAS). The non-inferiority margin was set to 0.3. Secondary outcomes included the patient's and investigator's judgment of global efficacy, the patient's rating of impairment of daily activities, and safety/tolerability of the treatments. RESULTS: Three hundred and six patients (mean age 53.5 years, approximately 60% female) were enrolled and randomized to the fixed combination cinnarizine/dimenhydrinate (n = 152) or betahistine (n = 154) groups; 297 patients completed the study and 294 (146 and 148, respectively) were valid for the per-protocol analysis, which was used for the non-inferiority analysis. Treatment with cinnarizine/dimenhydrinate led to a stronger reduction of the MVS [least squares mean (LSM)] after 4-week therapy (primary endpoint) in comparison to betahistine (0.395 vs 0.488; difference: - 0.093, 95% CI - 0.180; - 0.007, p = 0.035); since the upper limit of the two-sided 95% confidence interval was not only below the non-inferiority margin of 0.3, but also entirely below 0, superiority of the fixed combination could be demonstrated. The combination preparation was also more effective after 1 week of therapy and received more favorable patient's ratings on overall efficacy and impairment of daily activities. Both treatments were very well tolerated. Only 12 patients (3.92%) reported 13 non-serious adverse events; 2 cinnarizine/dimenhydrinate-treated patients discontinued the study prematurely due to adverse events as compared to 5 betahistine-treated patients. CONCLUSION: The fixed combination of cinnarizine 20 mg and dimenhydrinate 40 mg was found to be not only non-inferior, but superior to betahistine 16 mg in the improvement of peripheral vestibular vertigo. Furthermore, taking into account a good and slightly favorable safety profile, the present study provides evidence that the fixed-combination preparation is a potent and even superior alternative to betahistine in the treatment of vertigo related to peripheral vestibular disorders. STUDY REGISTRATION: EudraCT No. 2011-004025-27.
Keywords: vertigo; Young Adult; Drug Combinations; Male; mladý dospělý; Adolescent; Dimenhydrinate; betahistin; Cinnarizine; Adult; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; Vertigo; mladiství; dvojitá slepá metoda; senioři nad 80 let; lidé; cinarizin; ženské pohlaví; Humans; Aged, 80 and over; dimenhydrinát; Betahistine; Double-Blind Method; Female; fixní kombinace léků; lidé středního věku; Middle Aged; prospektivní studie